2015
DOI: 10.3168/jds.2014-9132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reference population size and available ancestor genotypes on imputation of Mexican Holstein genotypes

Abstract: The effects of reference population size and the availability of information from genotyped ancestors on the accuracy of imputation of single nucleotide polymorphisms (SNP) were investigated for Mexican Holstein cattle. Three scenarios for reference population size were examined: (1) a local population of 2,011 genotyped Mexican Holsteins, (2) animals in scenario 1 plus 866 Holsteins in the US genotype database (GDB) with genotyped Mexican daughters, and (3) animals in scenario 1 and all US GDB Holsteins (338,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The average length of the genome covered by ROH was 276.89 Mb for the population in this study, similar to that of Holstein cattle in the USA, where two studies demonstrated a covered genome’s length of 290.6 Mb and 299.6 Mb [ 30 , 31 ], which could be the reason for a higher estimation of the inbreeding degree for animals descending from dams of USA origin. This may be because the registered Holstein population of Mexico presents a high genetic relationship with the population in the USA [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average length of the genome covered by ROH was 276.89 Mb for the population in this study, similar to that of Holstein cattle in the USA, where two studies demonstrated a covered genome’s length of 290.6 Mb and 299.6 Mb [ 30 , 31 ], which could be the reason for a higher estimation of the inbreeding degree for animals descending from dams of USA origin. This may be because the registered Holstein population of Mexico presents a high genetic relationship with the population in the USA [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that reference population size is one of the primary factors affecting the quality of imputation [ 22 24 ]. Although the FImpute imputation algorithm works based primarily on long haplotype sharing, in the absence of that, there is an inherent probabilistic nature to imputation.…”
Section: Discussionmentioning
confidence: 99%
“…If high-density genotypes can be imputed reliably from low-density SNP arrays with sufficient accuracy, this would allow for the opportunity to genotype more animals in a more affordable way (García-Ruiz et al, 2015). Imputation is therefore an important statistical tool for enriching applications such as GWAS and GS that require higher or more evenly distributed marker densities (Marchini et al, 2007).…”
Section: Genotype Imputationmentioning
confidence: 99%